Reliability Analysis of In-person and Virtual Goniometric Measurements of the Upper Extremity - Tracy Spigelman; Leah Simpkins; Casey Humphrey; Yehor Vitel; Aaron Sciascia (North American Sports Medicine Institute, 2023)
# Background Virtual healthcare has forced clinicians to modify or eliminate parts of the musculoskeletal evaluation such as motion assessment. Although acceptable to excellent levels of in-person goniometric reliability is achievable, reliability of virtual assessments is unknown. # Purpose To determine if similar upper extremity goniometric measurements could be obtained in-person and virtually. # Study Design Reliability study; classroom setting # Methods Publicly recruited sample over 18 years of age with no upper extremity injuries. Each subject was tested in a standing position with dominant arm facing the clinicians to visualize the landmarks for goniometer placement. Flexion and extension of the shoulder, elbow and wrist were measured. Prior to performing in-person goniometric measurements for each joint, an image was captured of each pre-determined joint position using a mobile device with a camera. This image represented the screenshot on a virtual platform. Four clinicians performed in-person measurements twice during the same session on each subject. The following week clinicians measured virtual images using the same techniques. Inter-rater and intra-rater reliability were determined via intraclass correlation coefficients (ICC). # Results Inter-rater reliability for five of the six in-person (ICC≥0.81) and virtual measurements (ICC≥0.78 ) were classified as excellent. In-person wrist extension (ICC=0.60) and virtual wrist flexion (ICC=0.65) were classified as good. Intra-rater reliability for individual clinicians were between good and excellent for the in-person measurements (ICC:0.61-0.96) and virtual measurements (ICC:0.72-0.97). There were a greater number of excellent ICC values for the virtual measurements (90%) compared to in-person measurements (70%). There were statistically significant differences between in-person and virtual sessions for five of six measurements (p≤0.006). Only elbow extension did not differ between sessions (p=0.966). # Conclusion Virtual assessment compared to goniometric measurements showed good to excellent inter- and intra-rater reliabilities (ICC \> 0.60), which suggests clinicians can utilize goniometry either in person or on a virtual platform. # Level of Evidence 3b